Characterization and analysis of the interlaminar behavior of thermoplastic composites considering fiber bridging and R-curve effects. (November 2022) - Tijs, B.H.A.H.; Abdel-Monsef, S.; Renart, J.; Turon, A.; Bisagni, C.
Abstract: Thermoplastic composites can enable the development of new manufacturing techniques to make the aviation industry more sustainable while at the same time greatly benefit cost-efficient and high-volume production. One of the thermoplastic composite materials that can enable this transition is AS4D/PEKK-FC. In this work, the interlaminar properties of AS4D/PEKK-FC thermoplastic composite are characterized and analyzed by means of Mode I, II and Mixed Mode I/II at 50:50 tests, while considering fiber bridging and R-curve effects. In order to achieve stable crack propagation the test configurations are adjusted to account for the large fracture process zone ahead of the crack tip and an appropriate data reduction method is selected. The experimental data is reduced using an inverse methodology to extract cohesive laws based on only the load–displacement curves. Additionally, the use of this methodology provides new insights into the validity of two different mode II tests and the influence of fiber bridging on the mixed-mode interlaminar behavior. The interlaminar damage mechanisms are investigated by means of scanning electron microscopy. The resulting cohesive laws are implemented in commercial finite element software in tabular form, without the need for user-subroutines. All experimental test configurations are analyzed using a single material card and it is shown that fiber bridging and R-curve effects are well captured.